Karyotype comparison in two varieties of Vigna mungo L. after staining with orcein and CMA (Bangladesh Journal of Botany, 2008)
Two varieties of Vigna mungo viz. Barimash-1 and Barimash-3 were cytologically studied after staining with orcein and CMA. Both the varieties were found to possess 2n =22 metacentric chromosomes. Total length of diploid complements and range of chromosome length were more or less same in the two varieties. The orcein stained interphase nucleus of Barimash-1 had three big heterochromatic blocks, whereas Barimash-3 possessed several small heterochromatins. The orcein stained prophase chromosomes of Barimash-1 was darkly stained throughout the entire length. The gradual staining of prophase chromosomes were found in Barimash-3. The CMA stained interphase nuclei and prophase chromosomes of these two varieties were different. Sixteen entirely CMA banded chromosomes were found in Barimash-1. The percentage of GC-rich areas was 56.20. In Barimash-3, 11 entirely, 4 terminal and 4 centromeric fluoresced banded chromosomes were found. The percentage of GC-rich areas was 63.40. Although the two varieties showed similar conventional karyotypes, mark differences exist in their fluorescent karyotypes and the properties of interphase nuclei and prophase chromosomes. Therefore, these two varieties could be characterized with the help of modern cytological techniques. Â  Key words: Karyotype, Vigna mungo, Blackgram, CMA DOI = 10.3329/bjb.v36i2.1507 Bangladesh J. Bot. 36(2): 167-170, 2007 (December)